(untitled) - Sushama Sahoo; Sanjib Mandal (Asian Journal of Clinical Pediatrics and Neonatology, 2021)
Background: Hypoxic ischemic encephalopathy is a significant cause of neonatal morbidity and mortality and can lead to severe long term neurodeficits. There is a complex interaction of released neurotransmitters, altered electrolytes level and enzymatic activation. Without proper evaluation of biochemical changes, it is difficult to control its progression. The objective is to give an insight into correlation of severity with hypocalcemia and hyponatremia among HIE cases. Subjects and Methods: To conduct this cross sectional observational study serum sodium and calcium levels were measured in asphyxiated newborns who presented with seizure i.e HIE stage 2 and stage 3. Measured electrolytes levels were compared with severity of encephalopathy. Results: Results showed negative linear correlation of severity with both sodium and calcium levels but strength of association was more with sodium (r = -.631) than calcium (r = -.247). Also delay in presentation was more strongly associated with hyponatremia than hypocalcemia. Conclusion: Biochemical disturbances are very common in newborn with perinatal asphyxia. Among those who are presenting with seizures, hyponatremia is possibly more detrimental than hypocalcemia.